CHEMICAL AND FREE FATTY ACID COMPOSITION OF GOAT MILK CHEESE RIPENED WITH Lactobacillus acidophilus AND EXTRACT RABBIT STOMACH AS CO‐AGULANT - Nurliyani, Nurliyani (2014)
Rabbit   stomach   is   waste  from  rabbit   slaughtering  that   has  the   potential   to   be  used  as   an  alternative source   of   rennet   for  cheese   production.  The   purpose  of   this   study  was  to   determine  the   effect  of   ripen‐ ing   by  using  Lactobacillus   acidophilus   on  the   chemical   composition  and   free   fatty   acids  (FFA)   profile   of goat   milk   cheese   with   extract   of   rabbit   stomach   as   coagulant.   Lactobacillus   acidophilus   (1%)   was  inocu ‐ lated  into   pasteurized  goat   milk   and   incubated   for  1  h,    rennet   extract   up  to   3%  was  added   and   incu ‐ bated  for  25   min.    Cheese  was  stored   at   4 ο C  for  42  d.   The   moisture,  fat,   protein  and   ash  content  were analyzed   at   day  0,   21   and   42,  whereas  the   FFA   of   goat   milk   cheese   were  analyzed   on  day  0  and   42.  There were  significantly  differences   in   the   moisture,  protein, and   ash  content  in   the   goat   milk   cheese   on  21   and 42  days    of   ripening,   but  there  was  no  significant   difference  in   the   fat  content.   The   long ‐chain  saturated (C16:0   and   C18:0)   and   unsaturated  (C18:2)   FFA   were  the   most  abundant  in   goat   milk   cheese,  and   there were  no  significant   differences   between    pre  or   post   ripening.   The   concentration  of   short  chain  fatty acid   (C6:0,   C8:0   and   C10:0)   and   the   overall   concentration  of   FFA   in   goat   milk   cheese   after  42  days    rip‐ ening  was higher   compared  to   those   pre‐ripening.